Is aesthetic mind a plastic mind? Reflections on Goethe and Catherine Malabou - Valeria Maggiore (Aisthesis, 2019)
What is the relationship between thinking and seeing a form? In his morphological writings Goethe answers this question by saying that seeing is not pure passivity, but a thoughtful look because it invokes the mobility and plasticity of our thinking. For this reason this kind of aesthetic gaze is useful to understand the world of life, equally mobile and plastic. In this article, I will try to find out whether Goethe’s considerations about aesthetic idea and plasticity can find a new-look in the reflections of Catherine Malabou, one of the most influential thinkers in contemporary French debate, in whose works the concept of plastic form is central.